The impacts of the COVID-19 pandemic on social policies - Bonnet, Annabelle; Souza, Victor Neves de (Argumentum, 2021)
Editorial do volume 13, número 1, jan./abr.2021, sessão temática "Os impactos da pandemia COVID-19 sobre as políticas sociais"